Optic Flow and Tunnel Vision in the Detection Response Task. (September 2019) - van Winsum, Wim
Objective: In a driving simulator, a backwards counting task, a simple steering task, and a fully autonomous driving task were applied to study the independent effects of cognitive load, visual-cognitive-manual load, and optic flow on visual detection response task (vDRT) performance. The study was designed to increase the understanding of the processes underlying vDRT effects. Background: The tunnel vision effect induced by a "steering while driving" task found in a previous study was investigated further in this experiment. Method: Stimulus eccentricity and conspicuity were applied as within-subjects factors. Results: Cognitive load, visual-cognitive-manual load, and optic flow all resulted in increased vDRT response time (RT). Cognitive load and visual-cognitive-manual load both increased RT but revealed no interaction of task by stimulus eccentricity. However, optic flow resulted in a task by stimulus eccentricity interaction on vDRT RT that was evidence of a tunnel vision effect. Conclusion: The results suggested that optic flow may be a factor responsible for tunnel vision while driving, although this does not support the tunnel vision model because it is unrelated to workload. However, the results supported the general interference model for cognitive workload. Application: The results have implications for the diagnosticity of the vDRT. During driving tasks, tunnel vision effects may occur as a result of optic flow, and these effects are unrelated to workload.